Clasificación de los medios alternativos de comunicación en el proceso de enseñanza y aprendizaje virtual en la Parroquia Venus del Rio año 2020 - Diaz Fernandez, Roxana Isabel (2021)
The present study starts from a research problem: how the classification of alternative media influences the teaching-learning process in the Venus del Rio parish, these technological alternative media are currently becoming fundamental tools. Every year we can notice different changes in terms of communication and the year 2020 was no exception. After the confinement, we looked for ways to make use of different alternative means of communication, because with the passing of time, new forms of adaptation are acquired by people, reforms that evolve according to the increase of idioms which can be seen in the environment or in a society. The youth can acquire new habits easily and get used to these without complications making them part of their daily life, it is for this reason that when implementing the classification of alternative media in teaching and learning draws the attention of people for the different facilities that these can provide them. It is for this reason that the users of the parish Venus del Rio, have been satisfied with the use of the alternative means of communication, since it has benefited them a lot in education, communication and many other activities of their daily life. However, even though they did not count on this new modality of virtual classes, they now say that they feel more familiar with the alternative means of communication.